English in Science Textbooks - Kerur, Anagha (THE PRIMARY TEACHER, 2017)
There is a difference in the kind of English vocabulary and language used in literature and science textbooks. Students in the early classes, generally, learn the English alphabet, rhymes and few new words. As they reach higher classes, they are taught grammar and vocabulary, in terms of multiple meanings and complex sentence structures. But English language in science textbooks is entirely different from English textbooks even at the primary stage. So, children with a limited exposure to English language have to put in an extra effort to understand the terminologies and concepts as elaborated (in English) in the science textbooks. Many experience a ‘gap’ between the English they learn to speak and write, and that used in science textbooks. So, they need help in understanding the concepts explained in the textbooks, which many a time, they are unable to comprehend. Even if they happen to comprehend a concept, they are unable to articulate it fluently. This paper discusses how a little collaboration between science and English teachers can help the students understand the scientific terms and concepts discussed in the science textbooks better.